Dietary patterns and risk for gastric cancer: A case-control study in residents of the Huaihe River Basin, China - Wu, Xiaomin; Zhang, Qian; Guo, Hong; Wang, Ning; Fan, Xueqi; Zhang, Bin; Zhang, Wei; Wang, Wanying; Fang, Zhongze; Wu, Jing (Frontiers in Nutrition, 2023)
Abstract Aim: Evidence linking dietary patterns and the risk of gastric cancer was limited, especially in Chinese populations. This study aimed to explore the association between dietary patterns and the risk of gastric cancer in residents of the Huaihe River Basin, China. Methods: The association between dietary patterns and the risk of gastric cancer was investigated through a case-control study. Dietary patterns were identified with factor analysis based on responses to a food frequency questionnaire (FFQ). Gastric cancer was diagnosed according to the International Classification of Diseases, 10th Revision, (ICD 10). Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated across the tertiles of dietary pattern scores using unconditional logistic regression models. Results: A total of 2468 participants were included in this study. Six main dietary patterns were extracted, and those patterns explained 57.09% of the total variation in food intake. After adjusting for demographic characteristics, lifestyle factors, individual disease history, family history of cancer and Helicobacter. Pylori (H. pylori) infection, comparing the highest with the lowest tertiles of dietary pattern scores, the multivariable ORs (95% CIs) were 0.786 (0.488, 1.265; P trend < 0.001) for the flavors, garlic and protein pattern, 2.133 (1.299, 3.502; P trend < 0.001) for the fast food pattern, 1.050 (0.682, 1.617; P trend < 0.001) for the vegetable and fruit pattern, 0.919 (0.659, 1.282; P trend < 0.001) for the pickled food, processed meat products and soy products pattern, 1.149 (0.804, 1.642; P trend < 0.001) for the non-staple food pattern and 0.690 (0.481, 0.989; P trend < 0.001) for the coffee and dairy pattern. Conclusions: The specific dietary patterns were associated with the risk of gastric cancer. This study has implications for the prevention of gastric cancer.